Teaching of reading – writing in the Primary education: reflection from the learning difficulties - Puñales Ávila, Lucía; Fundora Martínez, Carlos Luis; Torres Estrada , Caridad Dariana (Atenas, 2017)
Transformations of the Cuban educational system intend to achieve the formation of children, adolescents and prepared youths in order to confront the changes of the present situation. In this context, the attention to the learning difficulties, as a way for assisting diversity, is necessary as an educative answer of primary school professionals. This theme is developed in the present research from a perspective of reading – writing teaching in first grade. The objective is to reflect around the necessity of the improvement of teaching – learning process of reading – writing in order to satisfy the potentialities of all the students.